Advancing the profession of academic advising for impactful practice (Journal of Student Affairs in Africa, 2026)
The Academic Advising Professional Development (AAPD) short learning programme is the only intervention that currently contributes to the professionalisation of academic advising in South Africa. To effectively and efficiently support student growth, development, and success, academic advisors need to develop a set of professional skills, knowledge, and behaviours. Only in combining continuous formal and informal professional training, development, and learning opportunities can students and institutions attain success. The AAPD is a contextualised formal training; it has borrowed from international literature and practice to assist academic advisors in acquiring the prerequisite knowledge and skills to develop intentional and responsive academic advising programmes, while refining their own advising values and philosophies. This article builds on and contributes to both international and national work in the field of academic advising as a practice and a profession. Additionally, it draws from Habley’s (1995) and McClellan’s (2007) conceptualisations of academic advising, which identify five core components that contribute to the professionalisation of advising. The application of these conceptual frameworks to map the content of the AAPD against key findings, has shown that while the AAPD provides a comprehensive introduction to the components of academic advising contextualised for the South African higher education landscape, early career participants still have a disjuncture in their understanding of the components. Therefore, the results of the study demonstrate that the AAPD framework does not only create opportunities to strengthen the existing components, but also reinforces additional components such as career advising, to advance the academic advising profession and practice within the South African context.
Keywords: academic advising; South Africa; professional development; practice, training